Engineered bio-nanocomposite magnesium scaffold for bone tissue regeneration. (August 2019) - Parai, Rohan; Bandyopadhyay-Ghosh, Sanchita
Abstract: Porous magnesium based materials are gaining intensive potential as a substitute scaffold material in the field of biomedical engineering as their mechanical properties such as compressive strength and elastic modulus are quite similar to that of human bone. Considering the poor mechanical integrity of ceramic and polymeric materials, metallic implants such as magnesium based alloy foams can be used as a promising scaffold material for bone tissue engineering. Magnesium foams also have properties like excellent biocompatibility and biodegradability so that revision surgery can be completely eliminated after implantation in orthopaedic applications. Against this background, porous Mg alloy based bioactive nano-composite foams were developed. Nano-hydroxyapatite (n-HA) was used as bioactive reinforcement which was anticipated to enhance bone tissue regenerations. Magnesium based alloy compositions were developed by incorporating selective alloying elements, while the bioactive nano-composite foams were fabricated using powder metallurgy route. The powder metallurgy route involved sequential stages of mixing and compaction of all powders with carbamide powder as a space holding material, followed by sintering of the green compacts. The microstructures of these nano-ceramic reinforced metal matrix foams were studied by scanning electron microscopy (SEM) in combination with energy dispersive X-ray spectroscopy (EDS), X-ray diffraction (XRD) and X-ray micro computed tomography (X-ray micro CT). Further, mechanical properties of the nanocomposite foams were evaluated. SEM and EDS results confirmed a homogeneous distribution of pores, alloying elements and n-HA. Structure–property correlations were established through the microstructural characterizations. The study therefore demonstrated that selected Mg alloy based composite foam can be an excellent candidate material for bone tissue engineering.